Transient and resident Salmonella: A genomic approach to analyzing over a decade of sampling events from fish meal production and storage facilities - Johnathan Likens; Jon W. Bell; Patricia Rabideau; Stephanie Haynes; Steven Wilson; Sandra Tallent; Eric W. Brown; Julie Haendiges (PLoS ONE, 2025)
This study evaluates Salmonella contamination in feed mill production facilities over a 12-year period, analyzing collection events from 12 facilities predominantly located in the southeastern United States. The genomic data reveals a historical contamination rate, with 20% of collection events testing positive for Salmonella. Utilizing next generation sequencing this study evaluated the genetic diversity in the different facilities to determine whether the Salmonella serovars that were found are transient or resident. Salmonella serovars Montevideo, Ruiru, and Senftenberg were frequently detected, with Ruiru showing a particularly high predominance across multiple facilities, suggesting possible common sources of contamination including regional fishing waters and shared additives. The study also highlights the role of transportation and storage methods as a possible cause of cross-contamination. Future research should focus on identifying specific contamination sources and optimizing control measures to reduce Salmonella risks in fish meal production.